PEMBANGUNAN APLIKASI SEBAGAI MEDIA PEMBELAJARAN BANGUN RUANG TINGKAT SD/SMP DENGAN MENGGUNAKAN METODE MARKER AUGMENTED REALITY - Nur Alamsyah; Rio Andriyat Krisdiawan (FKOM UNIKU, 2021)
Nowadays, the development of technology is growing so rapidly and the development can not be stopped. With a lot of advanced technology that popping up, various kinds of human work can be done in more innovative way. One of the example is in the field of education. Right now, there is a lot variety of learning media based technology, one of them is learning media using Augmented Reality technology or often shortened become AR. Application Development as Solid Shape Learning Media for Elementary School/Junior High School Level Using Marker Augmented Reality Method is one of utilization of the AR technology in the field of education, especially as learning media. By making solid shape learning media based Augemented Reality technology, students are expected to understand learning materials easily, and student’s learning interest can increased because the solid shape objects are build in attractive design colorful, and interactive to avoid boredom. Based on it, then this research become one of the new breakthrough in education field that utilizing the advancement of technology and help the teacher provide more interesting learning media. Meanwhile, the result of this research is an AR application and a solid shape mathematic book (handbook).Keywords : : Augmented Reality, Marker Augmented Reality, Learning Media, Solid Shape